A mirror to the world. Taking the German news magazine Der Spiegel into a topic modeling/sentiment perspective - Lino Wehrheim (Humboldt University Berlin, 2022)
The importance of mass media is reflected, among other things, in the fact that their coverage on certain topics - contrary to findings from communication research - is often seen as a reflection of the topics that are discussed by society. In Germany, this can be observed especially for the news magazine Der Spiegel, whose self-declared claim is to "hold up a mirror to the world". Accordingly, scholars from different disciplines frequently use its reporting, especially its cover stories, to support their own narratives, especially regarding general accounts on 'the zeitgeist'. Based on this observation, I propose the following thought experiment: suppose we were to look not only at individual cover stories with their individual topics, but at all cover stories - which picture of German contemporary history would then emerge? To answer this question, I use methods from the digital humanities / digital history to retrieve the topics and tonality of all cover stories published between January 1947 and December 2017. This way, I identify the topics that have dominated the Spiegel's front pages, which might be regarded as a trace or abbild of the narratives that shaped public discourse since the early days of the Federal Republic or even the zeitgeist itself.
urn:nbn:de:kobv:11-110-18452/25462-6
Keywords: N00; Z13; B40; 330; zeitgeist; narratives; media analysis; topic modelling; sentiment analysis